Pemodelan Regresi Logistik Ordinal Terhadap Faktor-Faktor Potensi Masyarakat Kota Semarang Mengalami Coronasomnia - Isna Nur Azizah; Anita Retno Indriani; Septi Winda Utami; Indah Manfaati Nur (Jurnal Karya Pendidikan Matematika, 2021)
Coronavirus is a disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Coronavirus spreads so fast which is caused depression, stress, and anxiety that triggers coronasomnia. Coronasomnia is a sleep problems because of COVID-19 pandemic. This research aims to determine factors that influence potential coronasomnia for people in Semarang City. The response variables that used in this case are two or more ordinal scale categories, so the analytical method is ordinal logistic regression. Based on the results and discussion, the equation obtained is Logit g2 (X) = 1,502 – 0,902X1(1) + 0,456X5 – 0,436X8 + 0,717X9 and Logit g3 (X) = 5,169 – 0,902X1(1) + 0,456X5 – 0,436X8 + 0,717X9. It can be concluded that there are four variables that affect potential coronasomnia for people in Semarang City, i.e gender, feelings of depression, worries about the future, and anxiety.